Integration of Project-Based Entrepreneurship and Productive Practical Learning in Vocational High Schools - Bayu Gilang Purnomo; Thomas Sukardi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
Unemployment rates producing by vocational high school (VHS) is still high. To overcome this problem, it is necessary to develop an entrepreneurship learning model in accordance with students’ skills. This study aims to: (1) develop project-based entrepreneurship learning media integrated with productive practical learning in VHSs; (2) design project-based entrepreneurship learning integrated with productive practical learning which had the criteria of validation, effectiveness, and practicability. The research procedures consisted of analysis, design, development, implementation, and evaluation (ADDIE) model. The product of the learning model development was validated by experts. The subjects of the research involved eleventh grade students of automotive engineering study program in the second semester, entrepreneurship teachers and automotive engineering teachers in VHSs. The products of the study consisted of: (1) a guided learning book and learning media (lesson plans and learning assessments); (2) the teachers’ and students’ positive and objective responses toward the implementation of the learning model which was proved by their comments that the developed learning model fulfilled the criteria of validation, effectiveness, and practicability to be implemented in VHSs.